Chinese and Japanese art : - Buhot, Jean (Frederick A. Praeger, 1967)
In this comprehensive and detailed survey of the history of Oriental art, Jean Buhot, who was for many years professor of Japanese at L'École du Louvre, traces the development of Chinese and Japanese art from prehistory to the present era. Its vast scope covers five millennia, beginning with the neolithic period of each civilization-describing the marble statues and inscribed bones of the Anyang excavations in China and the anthropomorphic funerary figures of the primitive Jomon culture in Japan.